Advances in Immuno-PET for the Detection of Cancer and Assessment of Response to Therapy - Alauddin, Mian M.; Khawli, Leslie A. (Current Medicinal Chemistry, 2021)
Background: Monoclonal antibodies (mAbs) against tumor-associated antigens have been shown to target tumors with specificity and selectivity; therefore, it was hypothesized that cancer could be treated with mAbs without side effects. In the early 1980s, clinical studies demonstrated that tumors could be visualized using radiolabeled mAbs. However, with the introduction of positron emission tomography (PET) with 18F-fluorodeoxyglucose (18F-FDG), antibody-based imaging became less important because of its limited diagnostic accuracy. During the last two decades, a revival of imaging with radiolabeled mAbs has taken place, specifically PET with longer half-life isotopes. Development of immune checkpoints as targets for immunotherapy has opened opportunities for the development of a wide variety of antibodies, such as anti-CTLA-4, anti-PD-L1, and anti-PD1. Thus, imaging with these antibodies radiolabeled with 89Zr or another long–half-life PET isotope, known as immuno-PET, has become mainstream. Objective: This study aimed to review the rapid development of immuno-PET for the detection of cancer and assessment of therapeutic response combining surgery, radiation, chemotherapy, and/or immunotherapy. This review includes reports on the radiolabeling, imaging and clinical utility of 89Zr-, 64Cu-and 124I-labeled mAbs. Results: More than 120 research and review articles on immuno-PET were reviewed. Conclusion: Many mAbs have been developed and used for the treatment of cancer; however, a limited number of antibodies have been radiolabeled for immuno-PET. While much progress has been made with the therapeutic applications of mAbs, immuno-PET for diagnosis and treatment assessment needs more research. Improved chelating agents and extensive imaging studies are needed to refine immuno-PET for the diagnosis of cancers and assessment of response to therapy.
Keywords: PET